A Case Series of Molecular Imaging of Glucagonoma After Initial Therapy—68Ga-DOTATATE PET/CT Reveals Similar Results as in Neuroendocrine Tumors of Other Origin in Follow-up and Re-evaluation. (April 2018) - Rottenburger, Christof; Papantoniou, Dimitrios; Mandair, Dalvinder; Caplin, Martyn; Navalkissoor, Shaunak
Abstract : Abstract: Glucagonoma is an extremely rare, glucagon-secreting neuroendocrine tumor of the pancreas. Only sparse data are available about the characteristics of this tumor in somatostatin receptor imaging and only for the situation of initial diagnosis. We present a series of 3 glucagonoma patients who underwent at least 1 68 Ga-DOTATATE PET/CT scan. All patients were diagnosed by either histology and/or elevated serum levels of glucagon. The presented cases suggest that somatostatin receptor–based imaging can probably be used for re-evaluation of disease status in patients with glucagonoma in a similar way as it is already established for neuroendocrine tumors of other origin.